The Emerald handbook of ethical finance and corporate social responsibility : a framework for sustainable development - Hunjra, Ahmed Imran; Hussainey, Khaled (Emerald Publishing Limited, 2024)
Ethical finance involves financial practices that consider environmental, social, and governance (ESG) factors affecting a borrower and/or its assets. This approach extends beyond traditional financial metrics, aiming to align investments and lending with principles promoting sustainability, social responsibility, and effective governance. While previously confined to specialized finance providers and investors supporting environmentally or socially focused enterprises, this paradigm has shifted into the mainstream. According to the Global Ethical Finance Forum, the management of ethically driven assets worldwide has exceeded $27 trillion, indicating a growing recognition of the importance of integrating ESG factors and values into financial considerations. Individual and professional investors increasingly acknowledge the pivotal role played by ESG variables in determining risk and reward. In the evolving landscape of investment and finance, ethical standards have become the norm, offering crucial safeguards for informed investment and finance decisions. Instances where funds and lenders are perceived to neglect appropriate ESG considerations in their decision-making processes now face heightened scrutiny and questioning. The Emerald Handbook of Ethical Finance and Corporate Social Responsibility: A Framework for Sustainable Development presents a novel perspective on ESG considerations and the implementation of Corporate Social Responsibility (CSR) for sustainable development. This approach carries global and enduring implications.